2009
DOI: 10.1016/j.actamat.2009.01.035
|View full text |Cite
|
Sign up to set email alerts
|

In situ and real-time 3-D microtomography investigation of dendritic solidification in an Al–10 wt.% Cu alloy

Abstract: The microstructural evolution of an Al-10 wt.% Cu alloy was investigated during solidification at constant cooling rate by in situ synchrotron X-ray microtomography with a resolution of 2.8 lm. Solidification of this alloy leads to a coarse dendritic microstructure which was fully characterized in terms of variation with temperature of the solid fraction, the specific surface area of the solid-liquid interface and the local curvatures of the solid phase. By analysing the evolution with solid fraction of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
100
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 17 publications
2
100
0
Order By: Relevance
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data. [20][21][22][23][24][25][26][27]29,30] …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, submicron resolution can easily be achieved on most synchrotron X-ray tomography beamlines. Combined with increasingly fast data acquisition systems, these techniques allow in situ microtomography observations of solidifying microstructures [14], even under tensile deformation [15].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In terms of microtomography, a thirdgeneration synchrotron radiation source provides partially coherent x-ray beam with enough brilliance to image a millimeter-sized sample at better than 10/micropixel resolution in a few seconds with high sensitivity. [10][11][12] In comparison to other nondestructive inspection techniques, such as magnetic resonance imaging, conventional micro-CT, and confocal microscopy, synchrotron-radiation-based micro-CT (SR-μCT) provides the unique capability of performing 3D dynamic studies. In SR-μCT, a synchrotron source can deliver intense x-rays over a wide energy spectrum, ranging from a few electrovolts to more than a hundred kiloelectrovolts.…”
Section: Introductionmentioning
confidence: 99%